Evaluating the activities of the computer book scheduled for the second year secondary students A Perspective of view of computer teachers and supervisors - Alsalmeen, Mohammed Ayed (Journal of Curriculum and Teaching Methodology, 2022)
The aim of this research is to know the level of estimates of computer teachers and supervisors for the activities of the computer book scheduled for students of the second grade of secondary school. The validity of the tool was confirmed by the validity of the arbitrators, and its stability was confirmed using the re-test method, and the research sample consisted of (30) teachers and supervisors who were chosen randomly. Arithmetic, standard deviation, percentages and frequencies to answer the study questions. The study reached the following results: 1-The evaluation level of computer teachers and supervisors of computer textbook activities for second grade secondary school students was low by 17% with regard to the diversity of book activities that take into account individual differences. 2-The evaluation level of computer teachers and supervisors’ evaluation of computer book activities for second year secondary students was low by 33% with regard to the suitability of book activities to the material and human capabilities available in the school environment. In light of the previous results, the research section is as follows: 1- Reducing some vocabulary of the computer book to suit the levels of second year secondary students. 2- Free training courses for teachers and supervisors to enable them to deal with the activities of the computer book. 3- Diversification of activities to take into account individual differences among students. 4- Providing butterflies and infrastructure